Nitric oxide and peroxynitrite exert distinct effects on mitochondrial respiration which are differentially blocked by glutathione or glucose. - Lizasoain, I (1996)
Nitric oxide (NO) and peroxynitrite both inhibit respiration by brain submitochondrial particles, the former reversibly at cytochrome c oxidase, the latter irreversibly at complexes I-III. Both GSH (IC50 =10 microM) and glucose (IC50 = 8 mM) prevented inhibition of respiration by peroxynitrite (ONOO-), but neither glucose (100 mM) nor GSH (100 microM) affected that by NO. Thus, unless ONOO- is formed within mitochondria it is unlikely to inhibit respiration in cells directly, because of reactions with cellular thiols and carbohydrates. However, the reversible inhibition of respiration cytochrome c oxidase by NO is likely to occur (e.g. in the brain during ischaemia) and could be responsible for cytotoxicity.